Distributed Efficient Joint Resource Allocation using Conjugate Gradient Method for Software-Defined Networking - Roshna, K; Jeetha, Rosiline (International Journal of Computer Sciences and Engineering, 2025)
Network operators run various applications on the control platform to perform different management tasks, like routing, monitoring, load balancing and firewall. These applications have complex interactions with each other, making it difficult to deploy and reason about their behaviours. To solve these kinds of problem, this paper presents a Distributed efficient joint resource allocation using conjugate gradient method (DEJRA-CG) is to accurately calculate the average energy consumption for all case in the dynamic network. The proposed method follows a SDN model for finding the Shortest Distances in gradient search estimation was formulated using three algorithms, namely Resource Allocation, Searching algorithm and Distributed Power Efficient Scheduling algorithm based on the identified network path in SDN. According to the experimental results the proposed algorithm mainly focused on SDN based caching and computing time using MATLAB R2013a platform. The achieved DEJRA-CG has less distance variation with less computation time when comparing to Building the Dependency Graph and software-defined networking, caching, and computing (SD-NCC) algorithms